2019
DOI: 10.1136/bjsports-2018-100195
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament (ACL) reconstruction and meniscal repair rates have both increased in the past 20 years in England: hospital statistics from 1997 to 2017

Abstract: ObjectivesWe investigated the temporal trend and the geographical variation in the rate of an anterior cruciate ligament (ACL) reconstruction and meniscal repair (MR) performed in England during a 20-year window.MethodsAll hospital episodes for patients undergoing ACL reconstruction or MR between 1 April 1997 and 31 March 2017 were extracted by procedure code from the national hospital episode statistics. Age-standardised and sex-standardised rates of surgery were calculated using Office for National Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 44 publications
1
56
0
1
Order By: Relevance
“…Meniscal repair has become a standard procedure accompanying ACLR over the last 2 decades [7,8]. Generally, it was shown that the outcome of meniscal repair performed at the same time as ACLR has better results than meniscal repair alone [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Meniscal repair has become a standard procedure accompanying ACLR over the last 2 decades [7,8]. Generally, it was shown that the outcome of meniscal repair performed at the same time as ACLR has better results than meniscal repair alone [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusive youth age window of ~ 6 to 25 is intended to overlap between periods when ACL injury prevalence and incidence are high and when youth are undergoing a state of heightened CNS plasticity. Data from the United Kingdom and Sweden show that ACL surgical repairs are most often performed in patients aged 20-29 [2,3]. However, surgical rates in patients under 20 years old are rapidly increasing, with reports from 1997 to 2017 indicating more than a 20-fold increase [2].…”
Section: Acl Injury and Neuroplasticity In Youth: An Overlapping Timementioning
confidence: 99%
“…Data from the United Kingdom and Sweden show that ACL surgical repairs are most often performed in patients aged 20-29 [2,3]. However, surgical rates in patients under 20 years old are rapidly increasing, with reports from 1997 to 2017 indicating more than a 20-fold increase [2]. The age window of surgical interventions for ACL injury is further modulated by sex.…”
Section: Acl Injury and Neuroplasticity In Youth: An Overlapping Timementioning
confidence: 99%
“…The exact incidence of ACL injury is not known as not all ACL injuries are diagnosed or proceed to surgery (Janssen, Orchard, Driscoll, & Van Mechelen, 2012). ACL surgical rates are often used as surrogate estimates of injury rates (Moses, Orchard, & Orchard, 2012;Sanders, Maradit Kremers, Bryan, Larson, et al, 2016), with rates of ACLR increasing worldwide (Abram, Price, Judge, & Beard, 2019;Sanders, Maradit Kremers, Bryan, Larson, et al, 2016;Zbrojkiewicz, Vertullo, & Grayson, 2018). An increasing ACLR rate is associated with increased work absenteeism, rehabilitation costs and an increased rate of degenerative knee conditions and knee joint arthroplasty (Barenius et al, 2014;Cinque, Dornan, Chahla, Moatshe, & LaPrade, 2017;Janssen et al, 2012;Khan et al, 2018;Suter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%